A Comparative Study of Three IR models for Bengali Document Retrieval - Chatterjee, Soma; Sarkar, Kamal (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we studied and examined some selected information retrieval approaches for Bengali information retrieval. These approaches used keyword to describe the content of each document. We choose three models to understand their working mechanisms and shortcomings. These models are TFIDF Vector Space model, Latent Semantic Indexing (LSI) model, and BM25 model. This understanding is important to overcome these shortcomings. These models are examined on our created Bengali dataset and Bengali queries and the results are stated in the result section in this paper. Our study reveals that Okapi BM25 model performs best among the three IR models studied for Bengali document retrieval